Employer’s Right And Liability Towards Migrant Worker’s Occupational Safety And Health In Malaysia - Landa, Azizah; Rahim, Rohani Abdul; Tajuddin, Muhammad Afiq Ahmad; Intung, Rovina; Makanah, Herlina; Bakar, Kamarudin Abu; Fandi, Fieza Fazlin (Universiti Sains Malaysia, 2016)

(untitled)
Malaysia is among the countries that use the services of many migrant workers in various work sectors. The rapid growth of the country that strived to be a developed country opens up many opportunities for migrant workers to come to work in Malaysia. The nature of the work performed by migrant workers usually involve high accidents risk work, in sectors such as construction, forestry, manufacturing and plantation. Their work involve heavy machinery, huge difficult to control instruments that may lead to accident risk. The cause of the accident may not only involve employees’ negligence but can also involve negligence on the part of employers. Unfortunately, when an accident occurred workers may be injured and died because of unexpected negligence and unsafe work systems. Therefore, when injuries or death occurred there are people who have to face legal action, incur criminal liability and are fined accordingly to the damage caused. This paper aims to discuss the employers’ rights and liabilities towards their migrant workers in terms of the occupational safety and health perspectives. These rights are provided in the legal provisions and the employers have responsibilities to ensure the safety and health system are managed and carried out effectively in workplaces. The discussion also focused on how employers’ leadership factors, can ensure safe work culture practiced at workplaces. Finally, remedial measures are suggested to provide rights and responsibilities to the employers to implement them in accordance with the existing legislation. The ultimate goal being to nurture a healthy and safe work culture among migrant workers and employers in Malaysia.